Mesoporous Silica Nanoparticles as Carriers for Intracellular Delivery of Nucleic Acids and Subsequent Therapeutic Applications - Cha, Wenzhang (Molecules, 2017)
Nucleic acids, including DNA, microRNA (miRNA), small interfering RNA (siRNA), and antisense oligonucleotide (ASO), are powerful gene regulators, which have been demonstrated as promising drug candidates for therapeutic treatments. Nevertheless, poor cellular membrane permeability and serum stability have greatly hindered the applications of nucleic acids in biomedicine. To address these issues, associate carriers that can encapsulate and protect nucleic acids are urgently required. Mesoporous silica nanoparticles (MSNs or MSNPs), which are nanomaterials with excellent biocompatibility, large surface area for functionalization, and tunable pore size for encapsulating different cargos, are emerging as novel and ideal biomaterials for different biomedical applications. In this review paper, we focus on the applications of MSNs in nucleic acid delivery and nucleic acid-guided therapeutic treatments. General strategies for the preparation of nucleic acid-MSN complexes will be firstly introduced, followed by a summary of recent applications of MSNs in nucleic acid delivery and nucleic acid-guided therapeutics.